Identidad y descolonización en el pensamiento katarista-indianista y la teoría decolonial (2017)
This work compares the concepts of the problem of identity and decolonialisationwith regards to the Katarista-Indianista beliefs and decolianisation theory. Bothconverge to see this phenomenon as an historical legcay that articulates politcaldomination, oppression, discrimation and the alienation of your own identity as aresult: but the decolonial focus framed the problem in a long lasting geopoliticalframework, the formation of modernity, eurocentrism and capitalism, thanks toit’s distinction between colonialism and coloniality. This difference has greatconsequences when the process of decolonilisation is considered, due to thefact that the decolonial ideologies suggest that the norm is to have a “different”society, distinct from the one that has been formed by the two parts of modernityand coloniality and based on interculturality, whilst the way of thinking of theKatarista-Indianista is heterogeneous.